Clean Stove Initiative Forum Proceedings, Phnom Penh, Cambodia, March 18, 2013 - World Bank (Washington, DC, 2014)
The East Asia and Pacific (EAP) clean stove initiative (CSI) forum is part of the World Bank's EAP CSI regional program, which focuses on achieving access to modern cooking and heating solutions in the EAP region, particularly through the scaled-up access to advanced cooking and heating stoves for poor, primarily rural households, who are likely to continue using solid fuels to meet their cooking and heating needs beyond 2030. The objectives of the EAP CSI forum are twofold. The first is to share results from implementing the first phase of the CSI, including reports on initial stocktaking activities in the four participating countries and the intervention strategies. The second is to promote collaboration, learning, and knowledge-sharing as the country initiatives move into their second phase. Market forces and mechanisms are powerful tools for ensuring a sustainable supply of clean cooking stoves and should be harnessed in a way that helps the private sector develop, market, and deliver modern cooking solutions. Thus, the CSI intervention strategy in each country needs to strike the right balance between market-based solutions, including innovative financing mechanisms (for example, results-based financing (RBF), with appropriately targeted subsidies. Government policies are needed to: (i) establish and maintain adequate levels of subsidies; and (ii) design and implement effective subsidy allocation mechanisms to mobilize and sustain private-sector participation in scaling up access to clean stoves. This paper is organized as follows: chapter one is Indonesia: toward universal access to clean cooking, key findings from the CSI; chapter two is Indonesia CSI program: government perspective; chapter three gives CSI implementation activity in Lao People's Democratic Republic (PDR); chapter four is China: toward universal access to clean cooking and heating, key findings from the CSI (phase one); chapter five presents development of clean stoves in China; and chapter six is millennium challenge account: Mongolia energy and environment project (2010 to 2013).